Clinical impact of post‐progression survival on overall survival in patients receiving nivolumab monotherapy as a second‐line treatment for advanced non‐small cell lung cancer. Issue 8 (24th February 2021) - Imai, Hisao; Yamaguchi, Ou; Mori, Keita; Hashimoto, Kosuke; Akagami, Tomoe; Shinomiya, Shun; Miura, Yu; Shiono, Ayako; Mouri, Atsuto; Kaira, Kyoichi; Kobayashi, Kunihiko; Kagamu, Hiroshi
Abstract: Background: The effect of second‐line treatment on overall survival (OS) may be affected by subsequent treatment in patients with non‐small cell lung cancer (NSCLC); however, in such patients, the correlation between post‐progression survival (PPS) and OS is unclear. Our study assessed the correlation of progression‐free survival (PFS) and PPS with OS, using individual patient data, in advanced NSCLC patients who were treated with second‐line nivolumab monotherapy, Methods: Between January 2016 and March 2019, we evaluated 92 NSCLC patients who received second‐line nivolumab treatment after first‐line platinum‐based combination chemotherapy. Using individual patient data, the correlations of PFS and PPS with OS were examined. Results: Linear regression and Spearman rank correlation analysis demonstrated that PPS was strongly correlated with OS ( r = 0.85, p  < 0.05, R 2 = 0.75), while PFS was moderately correlated with OS ( r = 0.65, p  < 0.05, R 2 = 0.42). Performance status at the beginning of second‐line treatment, immune checkpoint inhibitor rechallenge, and the number of treatment regimens used post‐progression, after the second‐line treatment significantly correlated with PPS ( p  < 0.05). In advanced NSCLC patients who underwent second‐line treatment with nivolumab, in comparison to PFS, there was a stronger correlation between PPS and OS. Conclusions: Our findings suggest that subsequent treatment for disease progression after a second‐line nivolumab treatment had a significant impact on OS. Abstract : Post‐progression survival (PPS) influences overall survival (OS) in NSCLC patients who receive second‐line nivolumab monotherapy. When compared with PFS, PPS was more strongly correlated with OS. Subsequent treatment after disease progression following second‐line nivolumab treatment had a significant impact on OS.